Competitive Creativity Between Talent Management and Service Quality: Evidence from Jordan Information Technology Sector - Alabbas, Marwan Mowaffaq Ghazi; Daud, Dazmin; Adnan, Wardatul Hayat (UUM Press, 2024)
Talent management encompasses a wide range of human resources management practices aimed at attracting and developing talented employees. This study examines the impact of talent management on service quality in Jordanian information technology companies, focusing on the perspective of talented employees and the role of competitive creativity. Data was collected from 341 employees at thirty different Jordanian companies using stratified random sampling techniques. The collected data was then analyzed using SPSS and AMOS SPSS analysis techniques to test the conceptual framework. The study findings demonstrate a significant positive impact of talent management on improving service quality, mediated through the indirect influence of competitive creativity. Furthermore, the direct effects of talent management practices such as talent attraction and talent succession planning were found to have a significant positive effect on service quality. On the other hand, the study reveals that other talent management practices, such as talent development, have a negative direct effect on service quality. Given that this study is the first to investigate the mediating role of competitive creativity between talent management and service quality in Jordan, the limitations of the study were carefully considered.